Carbonaceous chondrite meteorites as a record of protoplanetary disk conditions. Issue Volume 15:Issue S350(2019) (April 2019) - Russell, Sara S.; Bonato, Enrica; Bates, Helena; King, Ashley J.; Almeida, Natasha V.; Schofield, Paul F.
Abstract: Chondritic meteorites, and especially the most volatile-rich chondrites, the carbonaceous chondrites, preserve a record of the solar protoplanetary disk dust component and how it has been changed both in the disk environment itself and in its asteroidal parent body. Here we review some of the key features of carbonaceous chondrites and report some new data on their organics component. These show that the nebula reached temperature of >1000 0 C, but only very locally, to produce chondrules. Most meteoritic material underwent thermal and/or aqueous processing, but some retain delicate nebular components such as complex organic molecules and amorphous silicates.